Dual‐Isolation and Profiling of Circulating Tumor Cells and Cancer Exosomes from Blood Samples with Melanoma Using Immunoaffinity‐Based Microfluidic Interfaces. Issue 19 (19th August 2020) - Kang, Yoon‐Tae; Hadlock, Thomas; Lo, Ting‐Wen; Purcell, Emma; Mutukuri, Anusha; Fouladdel, Shamileh; Raguera, Monica De Silva; Fairbairn, Heather; Murlidhar, Vasudha; Durham, Alison; McLean, Scott A.; Nagrath, Sunitha
Abstract: Melanoma is among the most aggressive cancers, and its rate of incidence continues to grow. Early detection of melanoma has been hampered due to the lack of promising markers for testing. Recent advances in liquid biopsy have proposed noninvasive alternatives for cancer diagnosis and monitoring. Circulating tumor cells (CTCs) and cancer‐exosomes are gaining influence as promising biomarkers because of their cancer‐associated molecular markers and signatures. However, technologies that offer the dual‐isolation of CTCs and exosomes using a single sample have not been thoroughly developed. The dual‐utilization OncoBean (DUO) device is conjugated with melanoma specific antibodies, MCAM and MCSP, enabling simultaneous CTC and exosome isolations. Using blood samples from patients, CTCs and exosomes are specifically isolated from a single sample and then undergo molecular profiling for comprehensive study. Melanoma patients have 0–17CTCs mL −1 and 299 µg exosomal protein mL −1 while healthy donors display fewer than 2CTCs and 75.6 µg of exosomes mL −1, respectively. It is also demonstrated that both markers express melanoma‐associated genes using multiplex qRT‐PCR to test for expression pattern of a 96 gene panel. The dual isolation and molecular characterization will allow for further research into melanoma to identify viable markers for disease progression and treatment efficacy. Abstract : Circulating tumor cells (CTCs) and cancer exosomes are gaining influence as promising biomarkers in liquid biopsy, however, technologies that offer the dual‐isolation of CTCs and exosomes have not been developed. Here, a microfluidic device is devised conjugated with melanoma cell adhesion molecule (MCAM) and melanoma‐associated chondroitin sulfate proteoglycan (MCSP) for isolation and molecular profiling of both melanoma CTCs and exosomes.